A Proposed New Index for Clinical Evaluation of Interproximal Soft Tissues: The Interdental Pressure Index - Checchi Luigi; Montevecchi Marco; Marucci Gianluca; Checchi Vittorio (International Journal of Dentistry)
The interdental pressure index (IPI) is introduced to specifically evaluate clinical interproximal-tissue conditions and assess the effect of interproximal hygiene stimulation. This index scores clinical responses of periodontal tissues to the apical pressure of a horizontally placed periodontal probe. It is negative when gingival tissues are firm, bleeding-free, and slightly ischemic by the stimulation; otherwise it is positive. The clinical validation showed high intraoperator agreement (0.92; 95% CI: 0.82–0.96; P=0.0001) and excellent interoperator agreement (0.76; 95% CI: 0.14–1.38; P=0.02). High internal consistency with bleeding on probing (κ=0.88) and gingival index (Cronbach’s α=0.81) was obtained. Histological validation obtained high sensitivity (100%) and specificity (80%) for IPI+ toward inflammatory active form. The same results were recorded for IPI− toward chronic inactive form. IPI results as a simple and noninvasive method with low error probability and good reflection of histological condition that can be applied for oral hygiene motivation. Patient compliance to oral hygiene instructions is essential in periodontal therapy and IPI index can be a practical and intuitive tool to check and reinforce this important aspect.